1994
DOI: 10.1126/science.8134838
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Solution Structure of the β Chemokine hMIP-1β by Multidimensional NMR

Abstract: The three-dimensional structure of a member of the β subfamily of chemokines, human macrophage inflammatory protein-1β (hMIP-1β), has been determined with the use of solution multidimensional heteronuclear magnetic resonance spectroscopy. Human MIP-1β is a symmetric homodimer with a relative molecular mass of ∼16 kilodaltons. The structure of the hMIP-1β monomer is similar to that of the related α chemokine interleukin-8 (IL-8). However, the quaternary structures of the two proteins are entirely distinct, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
202
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(211 citation statements)
references
References 51 publications
8
202
1
Order By: Relevance
“…Essentially complete backbone and side-chain 1 H, 13 C, and 15 N chemical-shift assignments for bound MIP-1␤ and 1 H N , 13 C ␣ , 13 C ␤ , 13 CЈ, 15 N chemical-shift assignments for bound and free vCCI were obtained and are reported elsewhere (21,22). Deviation of chemical shift from random coil values allowed predictions of secondary structure for both protein components in the complex (23) and suggests that, in the complex, both proteins preserve the secondary structure elements that are present in their unliganded forms (7,19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially complete backbone and side-chain 1 H, 13 C, and 15 N chemical-shift assignments for bound MIP-1␤ and 1 H N , 13 C ␣ , 13 C ␤ , 13 CЈ, 15 N chemical-shift assignments for bound and free vCCI were obtained and are reported elsewhere (21,22). Deviation of chemical shift from random coil values allowed predictions of secondary structure for both protein components in the complex (23) and suggests that, in the complex, both proteins preserve the secondary structure elements that are present in their unliganded forms (7,19).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the differences in amino acid composition and functionalities, most chemokines share a remarkably conserved tertiary structure, with an extended N terminus followed by three ␤-strands in a Greek key arrangement and a C-terminal ␣-helix. The solution structure of the human CC chemokine MIP-1␤ (macrophage inflammatory protein 1␤) revealed a homodimer (7), and, subsequently, the dimer dissociation constant was determined to be 0.73 M (8). Dimerization of other chemokines has been observed under in vitro conditions, and the ability to dimerize is necessary for some chemokines to function in vivo (9).…”
mentioning
confidence: 99%
“…The naturally cleaved forms of MCP-2 and RANTES are also devoid of bioactivity (31,34). The function of chemokines has also been further clarified from crystal structure determination and nuclear magnetic resonance data (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). In several chemokines such as IL-8, MCP-1, MCP-2, MCP-3, eotaxin, RANTES, MIP-1␣, MIP-1␤, fractalkine, and stromal cell-derived factor-1, it has been observed that the N-terminal region is essential for functional activity and that the loop immediately following the first two cysteines in the sequence, as well as the N-terminal region, plays an important role in receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…The target function that is minimized during simulated annealing (as well as during conventional Powell minimization) comprises only quadratic harmonic terms for covalent geometry (that is bonds, angles, planes, and chirality), square-well quadratic potentials for the experimental distance and torsion angle restraints [37], an harmonic potential for the 3 JHN a coupling constant restraints [79,80], and a quartic van der Waals repulsion term for the non-bonded contacts [74, 81,82]. All peptide bonds were constrained to be planar and trans, with the exception of the peptide bond between Thr74 and Pro75 which was constrained to be planar and cis on the basis of the NOE data which unambiguously indicated the presence of a cs-proline.…”
Section: Structure 1994 Vol 2 Nomentioning
confidence: 99%